Aggregation kinetics of the Aβ1–40 peptide monitored by NMR. Issue 55 (16th May 2018) - Bellomo, Giovanni; Bologna, Sara; Gonnelli, Leonardo; Ravera, Enrico; Fragai, Marco; Lelli, Moreno; Luchinat, Claudio
Abstract : The aggregation of Aβ1–40 was monitored by solution NMR, which showed a trend complementary to the one observed by ThT-fluorescence. Abstract : The aggregation of Aβ1–40 was monitored by solution NMR, which showed a trend complementary to the one observed by ThT-fluorescence. The NMR data support a kinetic model where Aβ1–40 initially aggregates with the reversible formation of oligomeric species, which then irreversibly convert into fibrils.